IL “LINGUAGGIO FACILE TEDESCO”, IL “LINGUAGGIO FACILE ITALIANO”: UNA PROSPETTIVA SULLE STRATEGIE DI MEDIAZIONE (Italiano LinguaDue, 2023)
Il presente saggio analizza la produzione di testi in “Leichte Sprache” e in “linguaggio facile italiano” come attività di mediazione intralinguale (tedesco) e di traduzione interlinguale (tedesco – italiano). Dopo aver offerto un’introduzione sulla situazione a livello di legislazione, di codifica e di ricerca in Germania e in Italia, esso propone l’analisi di testi redatti in questa varietà, fra cui anche testi audiovisivi, ancora poco analizzati nella ricerca linguistica. L’analisi è rivolta alle strategie di mediazione utilizzate nella divulgazione delle informazioni di tipo politico, giornalistico e turistico. The ‘German easy language’, the ‘Italian easy language’: a perspective on mediation strategiesThis paper analyses the production of texts in “Leichte Sprache” (German Easy Language) and in “linguaggio facile” (Italian Easy Language) both as intralingual mediation (German) and as interlingual translation (German – Italian). After offering an introduction on the situation in Germany and Italy (legislation, codification, and research), it proposes the analysis of texts produced in this variety, including audiovisual texts, which are still little analysed in linguistic research. The analysis focuses on the mediation strategies used in the dissemination of political, journalistic and tourist information.